Therapeutic Strategies for MASH: An Update on Drug Candidates Under Investigation in Late-Phase Clinical Trials - Samuel Dinerman; Yan Shu (International Journal of Translational Medicine)
Metabolic dysfunction-associated steatohepatitis (MASH) is rapidly becoming a leading cause of hepatocellular carcinoma and end-stage liver transplantation. Characterized by hepatic steatosis, lobular inflammation, and hepatocyte ballooning, there is a dire need to develop therapeutic strategies to mitigate MASH alongside the subsequent fibrosis and cirrhosis. For years, therapeutic development for the treatment of MASH had been considered a graveyard, with various pharmacotherapies failing to achieve clinical efficacy. However, the recent Food and Drug Administration (FDA) approval of Madrigal Pharmaceuticals’ Resmetirom in the United States provides a positive step in the collective effort to eradicate MASH. Granted, with much about Resmetirom’s long-term efficacy and safety still to be determined and with the multi-factorial nature of MASH pathogenesis, continuing to evaluate alternative therapeutic options remains in the best interest of the field. Currently, therapeutics previously approved for other ailments, alongside novel therapeutics developed specifically for the treatment of MASH, are being evaluated in late-phase clinical trials. However, considering the complex nature of the disease and varying clinical outcomes to assess treatment efficacy, achieving regulatory approval as a MASH therapeutic continues to be a rigorous endeavor. In this review, we summarize notable therapeutics of various mechanistic backgrounds having achieved, or actively undergoing, late-phase clinical trials for the treatment of MASH and offer our perspectives on anti-MASH therapeutic development.